Feasibility of Flash Flipbook Media of Fungi Classification Based on the Fungi Inventory in Mount Pemangkat - Riska Maulidya; Laili Fitri Yeni; Titin Titin (Journal of Biology Learning, 2022)
This study aims to find out the feasibility of flash flipbook media based on the results of macroscopic fungi inventory found in the Mount Pemangkat Protected Forest, Sambas Regency. The form of research used is quantitative descriptive methods. The creation of flash flipbook media is enriched with the richness of local fungi found in the Protected Forest of Mount Pemangkat, Sambas Regency. Flash flipbook media is validated by five validators, including two lecturers of Biology Education Tanjungpura University and three high school teachers who were determined using purposive sampling techniques. Flipbook flash media validation sheets are assessed using the Likert scale and data analysis based on the Lawshe Formula (1975). Validation of flash flipbook media obtained a CVI (Content Validity Index) value of 0.94, so it is declared feasible and can then be used as a learning medium in the fungi classification sub-material and provide additional information about the diversity of mushrooms in the surrounding environment for students of class X high school.